(untitled) (Research, Society and Development, 2021)
The waste from health services (WFHS) are wastes from health care that go through a process of collection and special treatment to prevent the proliferation of diseases to the community and are properly disposed of ensuring the preservation of the environment. Due to the pandemic of Covid-19, declared by the World Health Organization (WHO) after an outbreak of pneumonia originating in the province of Hubei in China, there was a concern for the disposal of such waste from the assistance to patients with the disease due to the increase in their generation. The objective of this work is to clarify all the procedures that should be adopted so that such waste is sent to the proper treatment sites and final disposal in accordance with the Brazilian resolutions and laws for these managements, highlighting the main waste generated with the pandemic and the technical notes issued to face the calamity. In addition, it will be described how to draw up a management plan for health services waste (MPHSW), essential for the correct management of the waste generated.